Sacubitril/Valsartan Improves Left Atrial and Left Atrial Appendage Function in Patients With Atrial Fibrillation and in Pressure Overload-Induced Mice - Suo, Ya; Yuan, Meng; Li, Hongmin; Zhang, Yue; Li, Ying; Fu, Huaying; Han, Fei; Ma, Changhui; Wang, Yuanyuan; Bao, Qiankun; Li, Guangping (Frontiers in Pharmacology, 2019)
LCZ696 (Sacubitril/valsartan) is an angiotensin receptor-neprilysin inhibitor and has shown beneficial effects in patients with heart failure. However, whether LCZ696 protects against left atrial (LA) and LA appendage (LAA) dysfunction is still unclear. The present study aimed to assess the efficacy of LCZ696 for improving the function of LA and LAA. We performed both a retrospective study comparing LCZ696 with angiotensin receptor blockers (ARBs) to assess the efficacy of LCZ696 in patients with atrial fibrillation and an animal study in a mouse model with pressure overload. LA peak systolic strain, LAA emptying flow velocity, and LAA ejection fraction (LAAEF) were significantly increased in patients with LCZ696 as compared with ARBs (p=0.024, p=0.036, p=0.026, respectively). Users of LCZ696 had a lower incidence of spontaneous echocardiography contrast (p=0.040). Next, patients were divided into two groups (LAAEF ≤ 20% and > 20%). Administration of LCZ696 in patients with LAAEF > 20% was more frequent than LAAEF ≤ 20% (p=0.032). Even after controlling for LAA dysfunction-related risk factors (age, atrial fibrillation type, old myocardial infarction, hypertension, congestive heart failure, and prior stroke or transient ischemic attack), use of LCZ696 remained significantly associated with reduced probability of LAAEF ≤ 20% (odds ratio=0.011; 95% confidence interval [0.000–0.533], p=0.023). To further confirmed effect of LCZ696 in LA function, we constructed a post-transverse aortic constriction model in mice. Mice with LCZ696 treatment showed lower LA dimension and higher left ventricular ejection fraction and LAA emptying flow velocity as compared with mice with vehicle or valsartan treatment. Meanwhile, as compared with vehicle or valsartan, LCZ696 significantly decreased LA fibrosis in mice. In summary, we provide evidence that LCZ696 may be more effective in improving LA and LAA function than ARBs in both humans and mice, which suggests that LCZ696 might be evaluated as a direct therapeutic for atrial remodeling and AF.